Dinamika Perakaran Kakao (Theobroma cacao L.): Tinjauan Fisiologis, Agronomis, dan Pengelolaan Kebun - Bambang Budi Santoso; Jayaputra Jayaputra; I Komang Damar Jaya (LPPM Universitas Mataram, 2026)
Root growth dynamics in cacao (Theobroma cacao L.) play a critical role in determining water and nutrient uptake, supporting canopy development, and sustaining productivity under diverse environmental conditions. Unlike the canopy, which is relatively easy to observe, root growth is often overlooked because it occurs belowground. This review aims to synthesize current knowledge on the rhythmic growth of cacao roots, particularly fine roots, and their relationships with canopy growth, water availability, nutrient acquisition, shade systems, and orchard management. A narrative-integrative literature review was conducted using scientific articles, technical publications, and relevant research reports. The review indicates that cacao root growth is rhythmic and closely associated with shoot growth cycles. During leaf flushing, root activity may decline because assimilates are preferentially allocated to developing young leaves. Fine roots serve as the primary organs for water and nutrient uptake, but their growth and function are strongly influenced by soil moisture, aeration, organic matter, soil compaction, root competition with shade trees, and nutrient distribution in the rooting zone. Agroforestry systems may improve microclimate and soil conditions, yet they may also intensify belowground competition when shade tree species and spacing are not properly managed. This review emphasizes that cacao root management should include soil moisture conservation, fertilization based on active rooting zones, organic matter maintenance, shade regulation, and prevention of soil compaction and waterlogging. Understanding root growth rhythms is essential for developing productive, adaptive, and sustainable cacao orchard management.